(untitled) (Scholars’ Journal, 2020)
The purpose of this paper is to discuss the thesis writing practices of master’s level students in Nepali universities. To discuss the central issue and support the main argument of the paper, I relate some thesis writing anecdotes and experiences of master’s level students from the Nepali universities. The central argument of the paper is that thesis writing as a requirement to receive a degree at any cost is based on the traditional model which considers the process of writing as a highly mental and cognitive activity. As this model seems to be incapable of capturing the context in which the writing takes place, the socio-cultural theoretical orientation offering a more culturally sensitive view of academic writing practices has been increasingly gaining recognizable space in Nepali academia.